Synthesis and Crystal Structures of Stable 4-Aryl-2-(trichloromethyl)-1,3-diaza-1,3-butadienes - Seballos-Resendiz, Arturo; Lechuga-Eduardo, Harim; Barroso-Flores, Joaquín; Martinez-Otero, Diego; Romero-Ortega, Moises (Synthesis, 2016)
A simple and convenient method to generate 4-aryl-substituted 1H-2-(trichloromethyl)-1,3-diaza-1,3-butadienes from aryl(chloro)methaniminium salts (best known as Vilsmeier–Haack reagents) and trichloroacetamidine has been developed. These 4-aryl-1H-1,3-diazabutadienes are isolable, relatively stable during silica gel chromatography, and can be crystallized. The analysis by X-ray diffraction demonstrated that in the solid state these 1,3-diazabutadienes have an s-cisoid conformation. The principal characteristic of these 1,3-diazabutadienes is their reactivity towards electron-deficient acetylenes, reacting under mild reaction conditions to produce 4-aryl-2-(trichloromethyl)pyrimidines in good yields.
Keywords: diazadienes; cycloaddition; nitrogen heterocycles; Vilsmeier–Haack reaction; coupling reactions; imines